Economic and global warming impact assessment of biomass power generation in Thailand - Piyanon Haputta; Anchalika Pradeejit; Shabbir H. Gheewala (Center of Biomass & Renewable Energy (CBIORE), 2026)
To strengthen energy security, Thailand launched the Alternative Energy Development Plan (AEDP2018) in which the biomass energy production goal was set. The purpose of this study is to evaluate the economic and global warming impacts of power generation from biomass, including rice straw, rice husk, bagasse, and firewood, using input-output analysis. Five increasing biomass energy production scenarios are set corresponding to AEDP2018.The results show that biomass power promotion helps enhance Thailand’s economic growth. The highest growth of all scenarios is found when 3,500 MW of installed fossil-fuel capacity is replaced by biomass-based capacity from rice straw. The replacement leads to 0.058 percent increase in Gross Domestic Product (GDP) and 0.050 percent increase in total employment as compared to business-as-usual (BAU). Besides, the total greenhouse gas (GHG) emission of the country is lower than that of the BAU in every scenario, showing that the development of biomass power generation can help reduce climate change impact. As it provides the highest economic benefits and still has large remaining resource potential, rice straw should be prioritized for expanding biomass power generation, while firewood, bagasse, and rice husk should play supporting roles based on their advantages. Not only can the results of this study support Thailand’s transition toward a cleaner energy future, but also the method presented in this study can be a guideline for other developing countries aiming to expand renewable electricity from biomass.